Connecting cultural roots with mathematical thinking: A comprehensive meta-analysis of ethnomathematics practices in indonesian classrooms - Hartoyo, Agung; Fitriawan, Dona; Siregar, Nurfadilah; Ganda Putra, Fredi (Universitas Islam Raden Intan Lampung, INDONESIA, 2025)
Purpose: This study aims to synthesize empirical evidence on the impact of ethnomathematics-based learning on students’ mathematical achievement and attitudes in Indonesia and to examine how education level, mathematical domain, and cultural context influence learning outcomes. Method: A systematic review and meta-analysis were conducted following PRISMA and Cochrane standards on fifteen quantitative studies (n = 1,247) published between 2018 and 2024. A random-effects model was used to calculate effect sizes supported by heterogeneity and subgroup analyses. Findings: Results show a large positive effect on mathematical achievement (d = 1.15) and a moderate effect on learning attitudes (d = 0.69). Stronger impacts were found at the elementary level and in problem-solving tasks. Integrating local crafts, architecture, and traditional games enriched students’ engagement and conceptual understanding. Significance: The findings demonstrate that connecting cultural heritage with mathematics enhances cognitive mastery and positive learning attitudes. Ethnomathematics offers a culturally responsive framework that unites local wisdom with academic excellence, guiding educators and policymakers toward more inclusive and meaningful mathematics education.